Plastic mechanism models for use in DSM localised loading design of hat sections - Chen, Zhehang; Pham, Cao Hung; Hancock, Gregory J. (Thin-walled structures, 2025)
•Experiments on cold-formed steel hat sections subject to localised loadings are performed.•Plastic mechanism models for calculating yield load for hat sections subject to all localised loading cases are developed.•Direct strength method (DSM) equations are proposed for the design of hat sections with sloped webs.•A standardised calculation procedure is introduced for design engineers to calculate yield load for hat sections. The Direct Strength Method (DSM) of design has been recently developed for the design of cold-formed steel members under localised loading. The method requires a yield load (Py) and an elastic buckling load (Pcr) as input variables to the DSM design equations. This paper summarises test results used to develop plastic mechanism models for calculating Py for hat sections subject to practical loading cases. All four loading cases, including Interior Two Flange (ITF), End Two Flange (ETF), Interior One Flange (IOF) and End One Flange (EOF) loading cases were investigated. The yield/plastic mechanism behaviour of multiple web sections is not yet fully understood, while several publications in the literature have discussed the mechanical behaviour of hat sections under localised loading. Hence, this paper explains and proposes a plastic mechanism model based on the experimental data for calculating the yield load (Py) to be used in the DSM for localised loading design of hat sections in conjunction with the elastic buckling load Pcr.